Direct and Online Child Sexual Abuse: Prevalences and associated beliefs in Argentinean men - Bobbio, Antonella (2023)
It is estimated between 1 % and 5 % of young and adult men in the general population committed Child Sexual Abuse (CSA) at least once. The rates of those who admit to use Child Sexual Abuse Material (CSAM) are superior. This paper describes behaviors and beliefs associated with CSA in 345 Argentinean men who responded an Internet survey. At least one direct or online CSA behavior was reported by 6.3% of the participants. Specifically, 3.8% indicated having some behavior related to using CSAM. Most frequent beliefs associated with the use of CSAM in the sample referred mainly to the minimization of the damage suffered by children present in these images. Although some of these beliefs were significantly more prevalent in men with CSA, they were also present in men who did not report abusive behaviors. The importance of community studies and the need to primary and secondary prevention strategies that complement interventions in victims and prosecuted aggressors are discussed.